A missing piece of pancreas: A rare case report of dorsal pancreatic agenesis presenting as acute pancreatitis - Kuraning, Kiran; Sarada, Pooja Prathapan; Ganesh, K M; Chandan, Garud Suresh; Vijayan, Padmakumar Arayamparambil; Anbumani, Prasanth (Indian Journal of Case Reports, 2026)
There are various congenital anomalies of the pancreas, among which dorsal pancreatic agenesis is a very rare entity